(untitled) (Zaporizhzhia Historical Review, 2021)
The problems of integration and adaptation of German speaking Colonists in the Southern Ukraine, the peculiarities of cross-cultural dialogue of the representatives of German minority and native population of the region are taken into consideration in this article. The comparative analysis of the ìLebensweltenî of German speaking Colonists and Ukrainian peasants is stressed. The reasons of similarities and differences in responses of different ethnical and confessional groups of population in the Southern Ukraine in the 19th cent. to the challenges of the time are discovered.